Vulval carcinoma at the site of recent Bartholin gland excision: a rare case report - Kalpana, B.; Balamurugan, S. G.; Panda, Soumya Ranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Around 2-7% of all vulvar cancers are represented by primary carcinomas of Bartholin gland. Here we are presenting such a rare case of carcinoma of Bartholin gland. 45/F P2L2 presented in our OPD with non-healing lesion in vulva for 2 months. She had history of Bartholin’s cyst excision (elsewhere), 2 months back (the exact time since when she is having the non-healing lesion in vulva). Diagnostic biopsy revealed it to be vulval squamous cell carcinoma. She was given two cycles of Neo adjuvant chemotherapy (Inj. Paclitaxel and Carboplatin). In view of better response to the treatment patient was planned for surgery. Patient underwent wide local excision with bilateral inguinofemoral lymphadenectomy. Although the majority of vulvar lesions are benign, especially in women younger than 50 years of age, any solid mass should be carefully evaluated for malignancy. Preferably biopsy of Bartholin gland should be considered if the patient is more than 40 years of age and should be mandatory in a menopausal woman.